Adsorption of urea onto granular activated alumina: A comparative study with granular activated carbon. Issue 12 (2nd December 2018) - Safwat, Safwat M.; Matta, Minerva E.
ABSTRACT: This study investigated the ability of granular activated alumina to remove urea from wastewater through adsorption, and compared its performance with granular activated carbon. XRF, EDX, XRD, and TGA were used to investigate the adsorbents. The removal of urea as a function of pH value was studied. The point of zero charge for activated alumina was found to be 8.8, while that for activated carbon was found to be 7.1. The experimental data of the adsorption process were explored by fitting to different kinetic models to determine the adsorption kinetics and mechanisms. Then, the equilibrium data were examined by fitting to various two-parameter and three-parameter isotherm models. Results showed that the removal efficiency increased with the increasing pH value. The maximum removal efficiencies were 24% and 31% for granular activated alumina and granular activated carbon, respectively, at pH = 9.0. Kinetic studies showed that adsorption of urea onto both activated alumina and activated carbon can be expressed by pseudo second order kinetics. Equilibrium studies showed that the adsorption isotherms could be expressed by the Redlich-Peterson isotherm and Temkin isotherm for activated alumina and activated carbon, respectively. Adsorbents were investigated using FTIR and SEM, and results showed the occurrence of adsorption. GRAPHICAL ABSTRACT: